The protective immunity induced by intranasally inoculated serotype 63 chimpanzee adenovirus vector expressing human respiratory syncytial virus prefusion fusion glycoprotein in BALB/c mice - Huang, Lei; Liu, Mei-Qing; Wan, Chang-Qing; Cheng, Ning-Ning; Su, Yan-Bin; Zheng, Yan-Peng; Peng, Xiang-Lei; Yu, Jie-Mei; Fu, Yuan-Hui; He, Jin-Sheng (Frontiers in Microbiology, 2022)
Human respiratory syncytial virus (RSV) is a ubiquitous pediatric pathogen causing serious lower respiratory tract disease worldwide. No licensed vaccine is currently available. In this work, the coding gene for mDS-Dav1, the full-length and prefusion conformation RSV fusion glycoprotein (F), was designed by introducing the stabilized prefusion F (preF) mutations from DS-Cav1 into the encoding gene of wild-type RSV (wtRSV) F protein. The recombinant adenovirus encoding mDS-Cav1, rChAd63-mDS-Cav1, was constructed based on serotype 63 chimpanzee adenovirus vector and characterized in vitro. After immunizing mice via intranasal route, the rChAd63-mDS-Cav1 induced enhanced neutralizing antibody and F-specific CD8+ T cell responses as well as good immune protection against RSV challenge with the absence of enhanced RSV disease (ERD) in BALB/c mice. The results indicate that rChAd63-mDS-Cav1 is a promising mucosal vaccine candidate against RSV infection and warrants further development.